Towards social justice consciousness in Ghana’s higher education: Revisiting the thoughts of Nkrumah and Nyerere - Amuzu, Delali (Journal of Interdisciplinary Studies in Education, 2021)
This article revisits the thoughts of Kwame Nkrumah and Julius Nyerere on decolonizing higher education (university education) in Africa. Their selected scholarship centers on a critique of colonial higher education, arguing that it was designed to promote the economic aspirations of colonists. It was thus socially unjust, demeaned African realities, and not meaningful. For redemption, African universities should align with the aspirations of their societies and promote African consciousness. In spite of the relevancy of these perspectives, they are yet to firmly influence Ghana’s highAfrica, Decolonization, Educational Policy, Higher Education, Social Justiceer education policy. The thoughts are classified into the following themes: liberating the African mind, nurturing African character, owning the African narrative, and the use of knowledge. They are consequently recommended for policy considerations.